Pindar's library : performance poetry and material texts - Phillips, Tom (Oxford classical monographs, 2015)
'Pindar's Library' is the first volume to analyse the role played by Pindar's literary, cultic and scholarly reception in affecting readers' engagement with his poetry, considering the continuities between reading and attending performances, and highlighting elements of readers' experiences which were distinctive to Hellenistic culture